(untitled) (TSUL LEGAL REPORT, 2026)
This article stipulates that before making a decision that is an act of the judicial system protecting the violated rights, freedoms and interests, it is necessary to determine the actual circumstances of the civil case, as well as the qualification of these cases, ie to establish clear correspondence between the circumstances of the case. Before concluding on the existence of rights, freedoms and legitimate interests, the court must determine whether these legal norms are the existence of certain facts linking these rights, freedoms or legitimate interests, the evidence in civil proceedings, their admissibility, the need to prove them, The importance of the necessary reforms, the study of the legal nature of the assessment of evidence in the civil procedure legislation of the Republic of Uzbekistan, to identify existing problems and offer them legal solutions, following foreign experience, to solve this problem. issues of regulation and national legal regulation, the role and specific features of this area in the development of our national legislation, as well as the basics of legal regulation aimed at preventing potential risks in this area.